Legal Basis of Organizing Advertising Activity. - Berdiev J.K (Academia One, 2024)
This article discusses the legal framework for organizing advertising activities in Uzbekistan. In particular, the Law of the Republic of Uzbekistan "On Advertising" describes in detail the basic requirements for advertising. Also, this article reflects the tasks defined in the Decree of the Cabinet of Ministers of the Republic of Uzbekistan "On the regulation of the outdoor advertising market".
Keywords: Advertising; advertising activity; advertiser; outdoor advertising